2018
DOI: 10.1096/fj.201800917r
|View full text |Cite
|
Sign up to set email alerts
|

Insulin induces phosphorylation of pyruvate dehydrogenase through RhoA activation pathway in HepG2 cells

Abstract: Insulin is a critical signaling molecule in reducing blood glucose levels, and pyruvate dehydrogenase (PDH) is an essential enzyme in regulating glucose metabolism. However, the insulin effect on PDH function has not been well established. We observed that insulin attenuated the phosphorylation (p) of Ser264 (p-Ser264) in the PDH E1α subunit (PDHA1) in normal rat hepatocyte. In contrast, insulin induced an increase of p-Ser264 PDHA1 levels in hepatocellular carcinoma HepG2 and Huh7 cells. Insulin activated Rho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…In the human hepatocellular cancer cell line HEPG2, treatment with insulin, an upstream effector downregulating GSK3β, led to the activation of RhoA. In the same study, RhoA/ROCK1 was identified as a non-canonical pathway leading to GSK3β inactivation by insulin [131]. In contrast, it has been shown that in fibroblasts, GSK3β indirectly activated RhoA by phosphorylation and inhibition of RhoGAP, an upstream effector inactivating RhoA [111,132].…”
Section: Lamellipodia Filopodia and Invadopodia Formation And Dynamicsmentioning
confidence: 93%
“…In the human hepatocellular cancer cell line HEPG2, treatment with insulin, an upstream effector downregulating GSK3β, led to the activation of RhoA. In the same study, RhoA/ROCK1 was identified as a non-canonical pathway leading to GSK3β inactivation by insulin [131]. In contrast, it has been shown that in fibroblasts, GSK3β indirectly activated RhoA by phosphorylation and inhibition of RhoGAP, an upstream effector inactivating RhoA [111,132].…”
Section: Lamellipodia Filopodia and Invadopodia Formation And Dynamicsmentioning
confidence: 93%
“…Insulin was reported to increase p-Ser293 PDHA1 (p-PDHA1) levels in HepG2 and Huh7 hepatocellular carcinoma cells [ 14 ]. To elucidate a novel function of p-PDHA1 in HepG2 hepatocellular carcinoma cells, which are sensitive to insulin signaling, we identified the binding protein that may interact with p-PDHA1 using a recombinant GST phospho-mimic mutant PDHA1 Ser293Glu (S293D).…”
Section: Resultsmentioning
confidence: 99%
“…Endogenous expression levels of PKM2 and p-PDHA1 in each cell were different depending on the cell types, and they did not correlate with each other ( Figure 1 D). Insulin enhanced p-AKT level in HepG2 cells, suggesting insulin stimulates HepG2 cells in the classical pathway ( Figure 1 E) [ 14 ]. Of note, insulin augmented p-PDHA1 and PKM2 levels in HepG2 and Hepa1c1c7 ( Figure 1 F,G).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations